Towards Basic Sciences Curriculum Reform in General Medicine at Mashhad University of Medical Sciences - Seyed Isaac Hashemy; Haniye Mastour (Mashhad University of Medical Sciences, 2020)
Background: Integration is accepted as an important strategy in medical education and its final results depend on organizing different topics. In this method, the subjects (based on content) which are often included separately in a curriculum, are integrated in order to link and combine the content of the curriculum to create a cohesive learning experience. Development of this method is among the objectives of the medical education reform. Methods: The present applied cross-sectional study was performed on a statistical population (n=602) consisting of general medicine students of Mashhad University of Medical Sciences at the level of basic sciences. The participants were selected using the census sampling method and included 150 and 130 students who were admitted in February 2017 (the reformed curriculum) and in February 2016 (the conventional curriculum), respectively. The curriculums were compared in terms of learning outcomes and the number of vulnerable students. Moreover, the research hypotheses were tested using the independent t-test and chi-square test in SPSS software (version 22). Results: Based on the findings, with 95% confidence, the learning outcomes of the students who followed the reformed curriculum were better than those of the students who followed the conventional curriculum. According to the analysis of the collected data, the mean learning outcomes for the conventional and the reformed curriculum groups were 14.30±3.28 and 16.76±2.80 for the subject of anatomy, 14.10±2.62 and 15.13±2.93 for the subject of physiology, and 14.35±3.13 and 15.44±2.85 for the subject of biochemistry. However, no significant difference was observed in the number of vulnerable students in two groups. Conclusion: Based on the findings, basic sciences curriculum reform in medical education can improve the academic achievement of the general medicine students.